KARAKTERISTIK DAN MANAJEMEN DERMATITIS KONTAK ALERGI PASIEN RAWAT JALAN DI RUMAH SAKIT INDERA DENPASAR PERIODE JANUARI – JULI 2014 - Prabowo, Pratama Yulius (E-Jurnal Medika Udayana; Vol 6 No 8 (2017): E-Jurnal Medika Udayana, 2017)
Allergic contact dermatitis (DKA) is a common disease. No research has been done to find out the characteristics, and management of DKA in Denpasar. This study was conducted to determine characteristic and management of outpatients with DKA in Indera Hospital Denpasar in the period of January to July 2014. This study was retrospective and cross-sectional study. A hundred and six cases of allergic contact dermatitis at hospital from January to July 2014 was obtained. Seventy one cases were females (66.98%), 93 cases were patients with productive age (87.74%) and 24 cases were in the age range of 41-50 years (22.64%). DKA on hand was the most location found in this study, with 57 cases (53.77%). The most frequent complaint was itchy (96.23%). The most commonly-found efflorescence was erythema (75.47%). Most commonly-prescribed agents for DKA were topical preparations containing corticosteroids (99,06%) and oral anti-histamine (94,34%). Keywords: Allergic Contact Dermatitis , characteristic , management